Tribological Features of Refined, Deodorized, and Bleached Palm Olein with Mineral Oil Blend. Issue 4 (3rd July 2016) - Hassan, Mohammed; Ani, Farid Nasir; Syahrullail, S.
ABSTRACT: Vegetable oils have been investigated to replace petroleum-based lubricants due to their environmentally friendly characteristics, and these oils have become an important source of biolubricants. For the purpose of ensuring the ability of vegetable oils as a neat or partial biolubricants, image processing techniques were employed to explore the tribological characteristics of vegetable oil with a mineral oil blend. Refined, bleached, and deodorized palm olein blended with mineral oils was investigated using a four-ball tribotester and design of experiments with volumetric blend ratios of 20 to 80%. An optimized value E53.11/RB46.89 was obtained from the investigation, in compliance with ASTM D4172 standard. From the results, the E53.11/RB46.89 blend reduces the friction coefficient and wear scar diameter as well as the material lost in comparison with neat mineral oil. It is concluded that the E53.11/RB46.89 blend could be a potential partial biolubricant due to its negligible negative impact on wear and it provides satisfactory performance as a lubricant.